Mechanisms of change in cognitive-behavioral therapy for adults with binge-eating disorder: a dynamic structural equation modeling approach - Schmidt, Ricarda; Schewe, Danielle; Herpertz, Stephan; Zipfel, Stephan; Tuschen-Caffier, Brunna; Friederich, Hans-Christoph; Mayr, Andreas; Zwaan, Martina de; Hilbert, Anja (The international journal of eating disorders, 2025)
Objective Cognitive-behavioral therapy (CBT) is the most well-established treatment for binge-eating disorder (BED), but the mechanisms of change remain poorly understood. This study investigated in CBT for BED the effects of overvaluation of shape and weight and dietary restraint on subsequent objective binge-eating episodes (OBEs). Method In a multicenter randomized-controlled trial, 84 patients diagnosed with full- or subsyndromal BED were offered 20 individual sessions of CBT over 4 months. Dynamic structural equation modeling (DSEM) was used to disentangle within- and between-patient associations of overvaluation of shape and weight, dietary restraint, and OBEs. Results Between the first and last week of therapy, there were significant reductions in overvaluation of shape and weight, dietary restraint, and OBEs. DSEM showed significant within-patient effects of overvaluation of shape and weight on the subsequent number of OBEs. Weeks with lower overvaluation of shape and weight levels were followed by weeks with fewer OBEs. Although no within-patient effect of dietary restraint on OBEs was found, within-patient dietary restraint levels positively predicted subsequent overvaluation of shape and weight levels. Discussion The findings suggest that reductions in overvaluation of shape and weight may precede improvements in binge eating during CBT for BED, supporting its role as a potential mechanism of change. While dietary restraint did not show a direct temporal link to binge eating, its association with overvaluation points to a potential indirect role. These results underscore the value of targeting cognitive features of BED in CBT and highlight the need for more temporally sensitive assessments in mechanisms research.
Gesehen am 03.11.2025